A scoping review to map the concept, content, and outcome of wilderness programs for childhood cancer survivors. - Mats Jong; E Anne Lown; Winnie Schats; Michelle L Mills; Heather R Otto; Leiv E Gabrielsen; Miek C Jong (PLoS ONE)
Objectives Systematic mapping of the concept, content, and outcome of wilderness programs for childhood cancer survivors. Design Scoping review. Search strategy Searches were performed in 13 databases and the grey literature. Included studies describe participation of childhood cancer survivors in wilderness programs where the role of nature had a contextual and therapeutic premise. At least two authors independently performed screening, data extraction and analysis. Results Database searches yielded 1848 articles, of which 15 met the inclusion criteria. The majority of programs (73%) employed adventure therapy. Five activity categories were identified as components of wilderness programs: challenge/risk, free time/leisure, experiential learning, physical activity and psychotherapeutic activities. A majority of the participating childhood cancer survivors were female, white, aged 8-40 years, with a wide range of cancer diagnoses. Reported outcomes included increased social involvement, self-esteem, self-confidence, self-efficacy, social support, and physical activity. Key gaps identified included the absence of randomized controlled trials (RCTs), lack of studies on long-term effects, lack of information on the multicultural aspects of programs, and missing information on engagement in nature activities after the program ended. Conclusions This scoping review guides childhood cancer survivors, their families, practitioners, clinicians and researchers in the development and optimization of wilderness programs for childhood cancer survivors. In addition, it informs the utilization of these programs, and identifies gaps in the evidence base of wilderness programs. It is recommended that future study reporting on wilderness programs include more detail and explicitly address the role of nature in the program. Performing RCTs on wilderness programs is challenging, as they occur in real-life contexts in which participants cannot be blinded. Creative solutions in the design of pragmatic trials and mixed method studies are thus needed for further investigation of the effectiveness and safety of wilderness programs in childhood cancer survivors.